Financing Africa’s Post COVID-19 Sustainable Development: Domestic versus International Resources Mobilization - Aghem Hanson Ekori; Paul S. Masumbe (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
Even though the African continent has recorded the lowest deaths tolls caused by COVID-19, it is one of the slowest continents recovering from the pandemic. The effects of COVID-19 have crippled many developing progresses made prior to the pandemic and the government of many countries in the continent have already utilised the limited financial resources on the on-going crisis. Many African countries are seeking for financial assistance from institutions like the International Monetary Fund (IMF) the African Development Bank (AfDB), the World Bank and many other sources for post COVID-19 development. In financing Africa’s post COVID-19 development, this article will examines domestic public and private and international resource mobilization for Africa’s post COVID-19 development. It argues that both the revenues system of most African countries has to be restructured to ensure effective and efficient tax collection while reallocating more budgets for development. With regard to international resource mobilization, the Special Drawing Rights (SDRs) of the IMF, Foreign Direct Investment (FDI) were analysed. Similarly, the Strategy for Economic Governance in Africa (SEGA) of the AfDB and Agenda 2063 of the African Union (AU) were also examined as models for sustainable post COVID-19 development in Africa. Finally, it argues that financing post COVID-19 development will requires contributions from domestic, international private and public sources but the domestic financial sources should provide most of the funds because borrowing will enslave the borrower to the lender.